A Cross-Sectional Study of Risk Factors for Irritable Bowel Syndrome in Children 8–13 Years of Age in Suzhou, China - Xueping Zhu; Weichang Chen; Xiaoli Zhu; Yueping Shen (Gastroenterology Research and Practice)
To determine the prevalence and risk factors of IBS in children 8–13 years of age in Suzhou city, a cross-sectional study was conducted on children in grades 1 through 6 in public elementary schools in three districts of Suzhou. A multistage stratified random-sampling survey was conducted in a primary investigation using standardized questionnaires. Rome II criteria were used to confirm IBS and their risk factors were analyzed. Of 8,000 questionnaires 7,472 responded satisfactorily for a response rate of 93.4%. IBS was diagnosed in 10.81%. A decrease in the prevalence of IBS was significantly associated with advancing age and grade in school (trend test, P<0.05). The prevalence of IBS in females was higher but not significantly different than males. The significant risk factors for IBS included young age (OR = 0.94), food allergy (OR = 1.53), gastroenteritis during childhood (OR = 1.29), eating fried food (OR = 1.62), anxiety (OR = 1.49), psychological insults in early childhood (OR = 1.47), and parental history of constipation (OR = 1.81; all P<0.05). IBS prevalence of 10.81% in study population warrants preventive measures such as encouraging dietary changes, preventing gastroenteritis and childhood psychological insults.